Retinopathy of prematurity screening criteria and work load implications at Tygerberg Children's Hospital, South Africa: A cross-sectional study - Visser-Kift, Elsimé (Institute of Infectious Disease and Molecular Medicine, 2016)
High-income country ROP Screening guidelines are not appropriate for middle-income countries and screening requirements may vary even between units within one city. This study aimed to determine optimal ROP screening criteria, and its workload implications, for Tygerberg Children's Hospital (TCH), South Africa. Methods This cross-sectional study included premature infants screened for ROP, at TCH (1 January 2009 to 31 December 2014). Logistic regression for prediction and classification were performed. Predictors were birth weight (BW) and gestational age (GA). Endpoints were clinically significant ROP (CSROP) and Type 1 ROP (T1ROP).